Molecular Modeling and Simulation: An Interdisciplinary Guide An Interdisciplinary Guide - Schlick, Tamar (Interdisciplinary Applied Mathematics, 2010)
Review of previous edition: "I am often asked by physicists, mathematicians and engineers to recommend a book that would be useful to get them started in computational molecular biology. I am also often approached by my colleagues in computational biology to recommend a solid textbook for a graduate course in the area. Tamar Schlick has written the book that I will be recommending to both groups. Tamar has done an amazing job in writing a book that is both suitably accessible for beginners, and suitably rigorous for experts." J. J. Collins, Boston University, USA. "Molecular modeling ... is now an important branch of modern biochemistry. ... Schlick has brought her unique interdisciplinary expertise to the subject. ... One of the most distinguished characteristics of the book is that it makes the reading really fun ... and the material accessible. ... a crystal clear logical presentation ... . Schlick has added a unique title to the collection of mathematical biology textbooks ... . a valuable introduction to the field of computational molecular modeling. It is a unique textbook ... ." Hong Qian, SIAM Review, 2005.